Survei Seroprevalensi Taenia solium Sistiserkosis Di Kabupaten Mimika, Papua (SEROPREVALENCE SURVEY OF TAENIA SOLIUM CYSTICERCOSIS IN MIMIKA REGION, PAPUA) - Swacita, Ida Bagus Ngurah; Agustina, Kadek Karang; Polos, I Wayan; Fitriani, Sabelina; Natalia, Natalia (Buletin Veteriner Udayana; Vol. 7 No. 2 Agustus 2015, 2015)
Cysticercosis is an infection caused by the larval stage of pork tapeworm (Taenia solium)which still poses a public health problem. Papua is one of the largest endemic areas of cysticercosisin Indonesia. This survey aim was to determine the seroprevalence of cystisercosis in Mimikaregion, Papua. A total of 44 pig serum samples were collected from Kwamki Narama district (28samples), Mimika Baru (13 samples), and Kuala Kencana (3 samples) they were examined by using Enzyme Linked Immunosorbent Assay (ELISA). The result of the survey showed that theaverage of seroprevalence of cysticercosis in Mimika region, Papua was 50% (22/44), where thelargest seroprevalence found in the district of Kuala Kencana was 100% (3/3), District of KwamkiNarama was 46,4% (13/28), and district of Mimika Baru was 46,1% (6/13). It concluded that theseroprevalence of cysticercosis in Mimika was very high.Therefore,it is necessary to do moreintensive programs to prevent and control this disease.
Keywords: seroprevalence, cysticercosis, Taenia solium, papua